Delta/Alpha Ratio for Diagnosis of Autism Spectrum Disorder - Sverko, Z.; Vlahinic, S.; Vrankic, M.; Markovinovic, I. (2020 43rd International Convention on Information, Communication and Electronic Technology (MIPRO), 2020)
EEG data signal processing has been performed in order to outline the parameters for the comparison between participants with autism (5 subjects) and typically developing children acting as the control group (14 subjects). Based on the previous studies, the autistic group has a significantly higher delta/alpha ratio than the typical developing children. In this paper, we have tested this hypothesis on new participants. Furthermore, statistical features such as mean value, grand-mean value and their ratios have been calculated. The research was conducted by observing signals on electrodes F3, Fz, F4, C3, Cz, C4, P3, Pz and P4. We observed power delta-alpha, theta-high beta, theta-low beta, theta-alpha ratio, grand mean values of magnitude spectrum and 1 st moments of the grand mean values of the spectral distribution. The statistically significant difference between observed groups we found when tested 1 st moments of the grand mean values of the spectral distribution.